Korelacja etyki z gospodarką w doktrynie Herberta Spencera - Górecki, Olgierd (Annales. Etyka w Życiu Gospodarczym, 2010)
Herbert Spencer is one of the most distinguished representatives of Nineteenth-Century liberalism. Originality of his doctrine is based on combined concepts of social evolutionism with postulates of conservative liberalism. Ethics of an individual were the conceptual point of his philosophical reflection. Thus he believed that a free market economy is the economic foundation of ethical and material development of every individual. Material development may be summarized as achieving ever improving results of performed actions. According to Spencer, the free market critically assesses the quality of goods through increasing demand for goods of better quality. In this manner effective producers develop, because they achieve greater gain from their work. Moral development of an individual is in turn focused on continuous self-improvement. Through developing his skills a man increases the quality of actions carried out by him or of objects that he creates. The “law of equal freedom” – also described by Spencer – is in direct connection with the aforementioned issues. This rule states that every man has the right to do anything, as long as his actions do not infringe upon the freedom of another man which is defined in exactly the same manner. Thus the law of equal freedom can be characterized as a negative freedom if juxtaposed with relations that occur between individuals themselves or between individuals and the state. Combining of ethical and economic topics leads to the presentation of inhibitions that, according to Spencer, should be placed upon the activity of the State in the field of economy. Spencer believed that the State should not interfere with the economy, since all individuals should be granted full freedom of participating in comply with their own interests.